Dacomitinib antagonizes multidrug resistance (MDR) in cancer cells by inhibiting the efflux activity of ABCB1 and ABCG2 transporters. (1st May 2018) - Fan, Ying-Fang; Zhang, Wei; Zeng, Leli; Lei, Zi-Ning; Cai, Chao-Yun; Gupta, Pranav; Yang, Dong-Hua; Cui, Qingbin; Qin, Zuo-Dong; Chen, Zhe-Sheng; Trombetta, Louis D.
Abstract: The development of multidrug resistance (MDR) to chemotherapy remains a major challenge in the treatment of cancer. Numerous mechanisms have been recognized that cause MDR, but one of the most important mechanisms is overexpression of adenosine triphosphate (ATP)-binding cassette (ABC) transporters, through which the efflux of various anticancer drugs against their concentration gradients is powered by ATP. In recent years, small molecular tyrosine kinase inhibitors (TKIs) have been developed for treatment in various human cancers overexpressing epidermal growth factor receptor (EGFR). At the same time, some TKIs have been shown to be capable of inhibiting ABC transporter-mediated MDR. Dacomitinib (PF-00299804) is a second generation, irreversible TKI, which has shown positive anticancer activities in some preclinical and clinical trials. As many TKIs are substrates or inhibitors of ABC transporters, this study investigates whether dacomitinib could interact with ABC subfamily members that mediate MDR, including ABCB1 (P-gp), ABCG2 (BCRP) and ABCC1 (MRP1). The results showed that dacomitinib at 1.0 μM significantly reversed drug resistance mediated by ABCB1 and ABCG2, but not ABCC1, doing so by antagonizing the drug efflux function in ABCB1- and ABCG2-overexpressing cell lines. The reversal effect on ABCB1-overexpressing cells is more potent than that on ABCG2-overexpressing cells. In addition, dacomitinib at reversal concentration affected neither the protein expression level nor the localization of ABCB1 and ABCG2. Therefore, the mechanisms of this modulating effect are likely to be the following: first, as an inhibitor of ABCB1 or ABCG2 transporters, dacomitinib binds to drug-substrate site in transmembrane domains (TMD) stably in a noncompetitive manner; or second, dacomitinib inhibits ATPase activity and maintains the stability of TMD conformation in a concentration-dependent manner thereby inhibiting the drug efflux function of ABCB1 or ABCG2 transporter. This study provides a useful combinational therapeutic strategy with dacomitinib and substrates of ABCB1 and/or ABCG2 transporters in ABCB1- or ABCG2-overexpressing cancers. Highlights: Dacomitinib, a selective and irreversible inhibitor of EGFR has advanced to several Phase III clinical trials for the treatment of non-small-cell lung carcinoma (NSCLC). Dacominitib significantly enhanced the chemotherapeutic potential of anticancer drugs by blocking the function of ABCB1 and ABCG2 transporters. Molecular docking analysis suggests that Dacomitinib interacts with ABCB1 within its large cavity located in the transmembrane region. Combination of Dacomitinib and anticancer drugs can overcome ABCB1- or ABCG2-mediated drug resistance which is of great clinical interest.